(untitled) (Journal of the Society for Musicology in Ireland, 2020)
This article orientates an investigation of the late eighteenth-century fantasia around a case study of Mozart’s Fantasia in C Minor K.475, relating its findings to an array of historical contexts generating new insights into a genre, which remains ’an inherently problematic object of study’ compared to formally closed genres of sonata and rondo (Richards 2001:15). Musicological literature on the subject has focused mainly on keyboard fantasias by C.P.E. Bach (1714-1788) as well as on nineteenth-century fantasias by Beethoven, Schubert, Schumann, Liszt et al. The dearth of analytical engagement with the Mozartian model is perplexing, given its potential impact on the genre’s development; unlike the preceding free fantasias of C.P.E. Bach, K.475 combines structural logic and formal coherence with quasi-fantastical effects more typical of the Bachian fantasia. To this end, the article first provides a brief overview of musicological, theoretical and analytical contexts, drawing out conceptual frameworks in the work of Annette Richards (2001) and Matthew Head (2014), which have not yet been employed in a study of the Mozartian fantasia. The case-study analysis of K.475 that follows, engages critically with two established methodologies: Robert Gjerdingen’s schema theory (2007) and Schenkerian Analysis. Lastly, analytical discourse remains sensitive to the performance process, with a view to discovering if and how theoretical knowledge gained through analysis translates into a fantasia performance, and scrutinising ways in which performative introspection continues to influence a theoretical understanding of the piece.